Nuclear DNA content in some Chondrilla taxa (Asteraceae) of European Russia and Western Kazakhstan - Alena S. Parkhomenko; Mikhail V. Skaptsov; Anna O. Kondratieva; Saveliy F. Efimenko; Aleksandr S. Kashin (Acta Biologica Sibirica)
The aim of study was to evaluate the nuclear DNA content in samples of Chondrilla taxa from European Russia and Western Kazakhstan using flow cytometry approach. The analysis was performed in 30 populations of 8 taxa from the genus (C. brevirostris, C. laticoronata, C. juncea, C. latifolia, C. graminea, C. canescens, C. ambigua, and C. pauciflora). It was revealed that C. juncea, C. graminea, C. canescens and C. latifolia have the smallest monoploid genome size (1Cx) (1.078–1.098 pg), C. laticoronata and C. brevirostris have the intermediate values (1.190–1.203 pg), and C. pauciflora and C. ambigua have the largest (1.309–1.449 pg), i.e. the DNA content consistently increases by approximately 10% between these groups of taxa. The obtained results confirm the opinion that C. juncea, C. graminea, C. latifolia and C. canescens are synonymous with the priority name C. juncea. C. ambigua is the only one diploid species among the studied taxa. C. pauciflora is most likely its triploid cytotype. The position of C. laticoronata and C. brevirostris DNA contents between the C. juncea subspecies group, and the group including C. pauciflora and C. ambigua can be explained by distant hybridization that took place in the past, when C. ambigua or C. pauciflora acted as a maternal parent, and two species from the subgenus Chondrilla, different for each combination, acted as a paternal ones. The obtained results indicate that within the studied range the DNA content in Chondrilla at the interpopulation level changes regularly along the latitudinal gradient. From the south to about 50 °N, the genome size increases. From 50 °N to the north, the nuclear DNA content decreases.